2010
DOI: 10.1007/s00216-010-4079-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotubes for improved enantioseparations on a chiral ionic liquid stationary phase in GC

Abstract: In order to investigate whether the use of single-walled carbon nanotubes can improve enantioseparations on an ionic liquid stationary phase, a chiral ionic liquid, (R)-N,N,N-trimethyl-2-aminobutanol-bis(trifluoromethanesulfon)imidate, was synthesized. Two capillary columns, one containing the chiral ionic liquid and the other containing the single-walled carbon nanotubes and the chiral ionic liquid, were then prepared for GC. The results of the separations achieved with these columns show that coating the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…A significant enhancement of the enantioseparation of amlopdipine, propranolol, laudanosine, nefopam, sulconazole and ketoconazole has also been reported by using ionic liquid coating carbon nanotubes with a chiral selector ( Figure 7) [114,115]. Thus, SWCNTs provide a large inner wall for the interaction between the chiral selector and the analytes [37]. This achievement could be extended to more chromatographic columns and for the separation of a wider range of amino acids and chemical analytes in biological and chemical samples.…”
Section: Swcnts and Mwcnts For Chiral Separation In Biologicsmentioning
confidence: 81%
See 3 more Smart Citations
“…A significant enhancement of the enantioseparation of amlopdipine, propranolol, laudanosine, nefopam, sulconazole and ketoconazole has also been reported by using ionic liquid coating carbon nanotubes with a chiral selector ( Figure 7) [114,115]. Thus, SWCNTs provide a large inner wall for the interaction between the chiral selector and the analytes [37]. This achievement could be extended to more chromatographic columns and for the separation of a wider range of amino acids and chemical analytes in biological and chemical samples.…”
Section: Swcnts and Mwcnts For Chiral Separation In Biologicsmentioning
confidence: 81%
“…Scanning electron microscope images indicated that SWCNTs are attached end to end and produced a network skeletal-like structure [37]. In another experiment, enantioseparation of citalopram has been reported that utilised an ionic liquid coated MWCNTs for buffer modification in CE as compared with the same system without MWCNTs [114].…”
Section: Swcnts and Mwcnts For Chiral Separation In Biologicsmentioning
confidence: 99%
See 2 more Smart Citations
“…3) was described by Zhao et al, and the separation results showed that the capillary columns coated with the chiral ionic liquid stationary phase containing SWNTs improved the enantioselectivety. 51 A total of 12 racemates including DL-leucine, DL-isoleucine, (AE)-limonene, (AE)-2-phenyl-1-propanol, (AE)-phenylethanol, Fig. 2.…”
Section: Enantioseparation Based On Cntsmentioning
confidence: 99%